Hemorrhagic shock alters fracture callus composition and activates the IL6 and RANKL/OPG pathway in mice. Issue 2 (August 2018) - Bundkirchen, Katrin; Macke, Christian; Angrisani, Nina; Schäck, Luisa M.; Noack, Sandra; Fehr, Michael; Krettek, Christian; Neunaber, Claudia
Abstract : Background: Fracture and hemorrhagic shock often lead to impaired fracture healing. To elucidate underlying pathogenesis, this study aimed to analyze histological properties during fracture healing after hemorrhagic shock and involved signaling pathways in mice. METHODS: Male C57BL/6NCrl mice were assigned into five groups. Control group underwent no interventions. Sham group had a catheter and external fixator but neither blood loss nor osteotomy. Trauma-hemorrhage (TH) group received a pressure-controlled hemorrhagic shock; osteotomy (Fx) group, an osteotomy and fixator; and combined trauma (THFx) group, both hemorrhagic shock and externally fixed osteotomy. After 1, 2, 3, and 4 weeks, the animals were killed. Undecalcified bones were analyzed histologically and signaling pathways relevant for fracture healing by polymerase chain reaction and Western blot. Statistical significance was set at 0.05 or less. Comparisons were performed using the Mann-Whitney U or Kruskal-Wallis test. RESULTS: In the THFx group, a decreased bone formation after 3 weeks, a reduction of both bone and cartilage after 2 weeks, and an enhanced activation of the RANKL / OPG and IL6 signaling pathway after 1 week were shown in comparison to Fx. CONCLUSIONS: Hemorrhagic shock has a retarding effect on fracture healing in the early phase of fracture healing and leads to activation of the IL6 and RANKL/OPG signaling pathways. Abstract : Supplemental digital content is available in the text.